A prospective study of nut consumption and risk of primary hepatocellular carcinoma in the U.S. women and men - Sui, Jing (Cancer Prev Res (Phila), 2019)
Although increasing evidence suggests a potential beneficial effect of nut consumption on various diseases, no epidemiologic study has yet examined the association between nut consumption and risk of hepatocellular carcinoma (HCC). We prospectively examined this association in 88,783 women from the Nurses’ Health Study and 51,492 men from the Health Professionals Follow-up Study. Nut consumption was assessed every 4 years using validated food frequency questionnaires. Multivariable hazard ratios (HRs) and 95% confidence intervals (95% CIs) were estimated using Cox proportional hazards regression models after adjusting for HCC risk factors. After an average of 27.9 years of follow-up, we identified a total of 162 incident HCC cases. Higher total nut consumption was not significantly associated with HCC risk (the highest vs. lowest tertile intake, HR=0.84, 95% CI: 0.56–1.26). For the same comparison, higher tree nut consumption was associated with a lower HCC risk (HR=0.64, 95% CI: 0.43–0.95). We found non-significant inverse associations with consumption of walnuts, peanuts, and peanut butter. Overall, nut consumption was not strongly associated with HCC risk. There was a suggestive inverse association with tree nut consumption. Future studies should carefully consider hepatitis B or C virus infections and examine these associations in other racial/ethnic groups.